2012
DOI: 10.4103/0975-7406.94810
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of end stage renal disease patients undergoing hemodialysis

Abstract: Background:In India the incidence of end stage renal disease (ESRD) is increasing day by day and the option for the treatment of ESRD is dialysis or transplantation. In the present scenario, due to the cost of treatment normal people can afford only hemodialysis rather than transplantation. Since the cost of hemodialysis differs across the country, research is needed to evaluate its exact cost.Aim:This study is to analyze the healthcare cost of hemodialysis in a private hospital of South India.Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 22 publications
3
34
2
Order By: Relevance
“…Our analysis found three studies on the costs of dialysis in India. Suja et al [ 31 ] performed economic evaluation of ESRD patients undergoing HD at Amrita Institute of Medical Sciences, Kerala. Patient perspective was taken for the analysis of cost component and the details were collected by direct patient interview.…”
Section: Lower Middle-income Countriesmentioning
confidence: 99%
“…Our analysis found three studies on the costs of dialysis in India. Suja et al [ 31 ] performed economic evaluation of ESRD patients undergoing HD at Amrita Institute of Medical Sciences, Kerala. Patient perspective was taken for the analysis of cost component and the details were collected by direct patient interview.…”
Section: Lower Middle-income Countriesmentioning
confidence: 99%
“…These findings were consistent with other studies in which they found a positive correlation between income, employment and educational status. Financial constraints were less for upper and upper middle family that might be the major contributing factor for higher scores[23]. The higher educational status helps the patients to understand their illness in a better way and also about the importance of adherence to therapy.…”
mentioning
confidence: 99%
“…Although this cost component has been rarely assessed in COI studies on HD, the proportion found in this study is greatly lower than what was reported from other countries. [21,22,36,37] Beside differences in measurement and valuation methods, this finding might be attributed to the fact that 82.5% of the patients in our study were already unemployed or retired at the time of the analysis. Moreover, being prevalent patients, they already adapted their work schedules and daily life activities to their HD treatment, and the majority of them eventually managed to avoid losing additional hours of work or daily life activities due to their illness and its treatment.…”
Section: Discussionmentioning
confidence: 80%